Demonstrating the significance of radiant energy exchange during metal dust combustion. (March 2023) - Jones, Harrison; Dube, Pascal; Tran, Quan; Pantoya, Michelle L.; Altman, Igor
Abstract: Metal combustion is a process accompanied by strong light emission. Correspondingly, radiative loss can significantly affect the overall energy balance, and needs to be considered in the global numerical models describing metal dust combustion. In this work, we experimentally estimated the fraction of radiative loss during aluminum (Al) dust combustion by studying the heat release in a modified constant volume bomb calorimeter that enabled the additional measurement of pressure. The previously developed method of dispersing powder ensured nearly 100% combustion efficiency. The contribution of the combustion energy to heating the gas inside the calorimeter bomb was determined by analyzing the measured pressure traces and found to be measurably lower than 100%. The energy loss was attributed to radiant heat transfer from burning metal particles to the bomb wall. Aluminum powders with median size ranging from 4 μm to 100 μm were studied. The estimated fraction of radiative loss depended on the particle size. Radiative loss saturated at nearly 50% for larger particles and gradually reduced with the particle size decrease below 20 μm. We related the observed radiative loss to a recently introduced process that occurs during metal combustion, namely condense-luminescence. The results shown here have important implications for the role of radiant energy exchange in metal particle combustion and will transform future approaches to harnessing metal oxidation energy for a multitude of applications.